2020
DOI: 10.1111/jonm.13225
|View full text |Cite
|
Sign up to set email alerts
|

Defining a set of potentially preventable complications relevant to nursing: A Delphi Study among head nurses

Abstract: Aim To establish a list of potentially preventable complications as a tool for nursing management. Background Different outcome parameters have been used in patient safety research. However, they have mainly been used for medical and administrative goals. The role of nurses in achieving patient safety outcomes has been given little attention. Method A three‐round Web‐based modified Delphi study was conducted in four hospitals, using the list of potentially preventable complications (PPCs) as a starting point. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Results favorable to the use of different nasoenteral tube insertion methods have been described by anesthesiologists. [14][15][16] Among these, the lateralized head [4,15] and the use of the laryngoscope [4] stand out. Such studies have demonstrated small-bowel feeding tube insertion methods that are faster, more effective and that cause less complications to patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results favorable to the use of different nasoenteral tube insertion methods have been described by anesthesiologists. [14][15][16] Among these, the lateralized head [4,15] and the use of the laryngoscope [4] stand out. Such studies have demonstrated small-bowel feeding tube insertion methods that are faster, more effective and that cause less complications to patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the piriform sinus and the arytenoid cartilage are considered anatomical obstacles for the nasally placed small-bowel feeding tube passage, which is sometimes bended in the oral cavity due to the inability to swallow and the presence of the endotracheal cannula cuff. [4] Therefore, AEs such as accidental tube displacement, wrong positioning in the respiratory tract, tube obstruction, inadvertent exit, bronchoaspiration and connection route errors can occur during this procedure. [5,6] Among serious and fatal AEs, pneumothorax, aspiration pneumonia and pulmonary hemorrhage stand out.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation